Trade policies in Latin America and the Caribbean : priorities progress and prospects - Rajapatirana, Sarath (International Centre for Economic Growth San FranciscoUS, 1997)
Documents the wide ranging reform of trade policies undertaken by the Latin America and Caribbean governments from the early 1980s to mid-1995. Deals with the trade policy problems faced by the countries in the region, progress achieved in trade policy reforms and prospects for the future.